Ethics and public management: A view from the other side - Cárdenas Krenz, Ronald (2008)
The present article displays an ample overview of the public function, its importance, access to it, difficulties it has been experiencing (mainly with the corruption), and the problems that the funtionaries go throught on a daily basis in their professional performance. We also comment the codes of ethics that several institutions have been developing as a form to face the problem of corruption; it is also needed that the legitimacy of the institutions does not rest solely on their norms, but on their effective application